2023
DOI: 10.1186/s43058-023-00472-w
|View full text |Cite
|
Sign up to set email alerts
|

Similar skills, different frames: a thematic analysis exploring conceptualizations held by community-based organization practitioners and academics regarding skills to use evidence-based interventions to address cancer inequities

Shoba Ramanadhan,
Jennifer L. Cruz,
Maggie Weese
et al.

Abstract: Background Community-based organizations (CBOs) are critical partners in delivering evidence-based interventions (EBIs) to address cancer inequities. However, CBO practitioners do not typically have access to opportunities to build the necessary capacity (skills, knowledge, motivation, and resources) for using EBIs. Although capacity-building interventions can offer a solution, inconsistent definitions and measurements of capacity limit the ability to develop and evaluate such efforts. We explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This emphasis may reflect the inclusion of practitioners in this exercise. The formative work for this project and our early explorations of the data suggest that the five-cluster solution identified based on all participants’ data may mask important differences between academics and practitioners in their conceptualization of core skills and areas of need for capacity-building [ 11 ]. Similar to other group concept mapping studies involving academic and community groups [ 31 ], important distinctions in the conceptual thinking of the two subgroups may have implications for design, uptake, and sustainability of EBIs at the local level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasis may reflect the inclusion of practitioners in this exercise. The formative work for this project and our early explorations of the data suggest that the five-cluster solution identified based on all participants’ data may mask important differences between academics and practitioners in their conceptualization of core skills and areas of need for capacity-building [ 11 ]. Similar to other group concept mapping studies involving academic and community groups [ 31 ], important distinctions in the conceptual thinking of the two subgroups may have implications for design, uptake, and sustainability of EBIs at the local level.…”
Section: Discussionmentioning
confidence: 99%
“…CBO practitioners grounded their discussions of skills in community needs and long-term health promotion goals. In contrast, academics tended to focus on the EBI and other system attributes related to the technology being transferred [ 11 ]. Over the last decade, our team and colleagues have repeatedly found that CBO practitioners and academics often understand research evidence, EBIs, and opportunities to build capacity for EBI use in meaningfully different ways [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%